2014
DOI: 10.3390/ijms15045508
|View full text |Cite
|
Sign up to set email alerts
|

Transgene IL-6 Enhances DC-Stimulated CTL Responses by Counteracting CD4+25+Foxp3+ Regulatory T Cell Suppression via IL-6-Induced Foxp3 Downregulation

Abstract: Dendritic cells (DCs), the most potent antigen-presenting cells have been extensively applied in clinical trials for evaluation of antitumor immunity. However, the efficacy of DC-mediated cancer vaccines is still limited as they are unable to sufficiently break the immune tolerance. In this study, we constructed a recombinant adenoviral vector (AdVIL-6) expressing IL-6, and generated IL-6 transgene-engineered DC vaccine (DCOVA/IL-6) by transfection of murine bone marrow-derived ovalbumin (OVA)-pulsed DCs (DCOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In contrast to strategies aimed at improving the immunogenicity of endogenous melanoma-associated DC, approaches to enhance the immunostimulatory capacity of exogenous DC have also improved the efficacy of many melanoma vaccines. For example, strategies that provide immune stimulating support for exogenous DC, such as the introduction of IL-6 or IL-21 transgenes into BMDC ( 137 , 138 ) or the co-administration of oncolytic adenovirus engineered to express immune stimulators such as IL-12 and GM-CSF ( 64 , 119 ), have been shown to significantly improve vaccine efficacy, resulting in complete regression of established melanomas in some cases. Combinatorial approaches that aim to neutralize the effects of tumor-derived factors on exogenously administered DC, such as local siRNA-mediated silencing of TGFβ1 at the tumor site ( 139 ), have also been effective.…”
Section: Interfering With Immunosuppressive Network That Impair the mentioning
confidence: 99%
“…In contrast to strategies aimed at improving the immunogenicity of endogenous melanoma-associated DC, approaches to enhance the immunostimulatory capacity of exogenous DC have also improved the efficacy of many melanoma vaccines. For example, strategies that provide immune stimulating support for exogenous DC, such as the introduction of IL-6 or IL-21 transgenes into BMDC ( 137 , 138 ) or the co-administration of oncolytic adenovirus engineered to express immune stimulators such as IL-12 and GM-CSF ( 64 , 119 ), have been shown to significantly improve vaccine efficacy, resulting in complete regression of established melanomas in some cases. Combinatorial approaches that aim to neutralize the effects of tumor-derived factors on exogenously administered DC, such as local siRNA-mediated silencing of TGFβ1 at the tumor site ( 139 ), have also been effective.…”
Section: Interfering With Immunosuppressive Network That Impair the mentioning
confidence: 99%
“…AdV expressing the gene IL‐6 was constructed by inserting the mouse IL‐6 gene (cloned from ConA‐stimulated T cells into pShuttle vector) to form pLpA IL‐6 (using the cloned IL‐6 cDNA) expressing IL‐6 gene . The Pme I‐digested shuttle vector was then co‐transformed into BJ5183 Escherichia coli cells containing the backbone vector for homologous recombination to form the recombinant vector AdV IL‐6 .…”
Section: Methodsmentioning
confidence: 99%
“…Cytokines act as messengers at the interface of innate and adaptive immunity and are released in response to a variety of stimuli, including injury, infection and inflammation . We have recently demonstrated that transgene IL‐6 ‐engineered DCs up‐regulated the expression of DC maturation markers, secreted transgene‐encoded IL‐6 and more efficiently stimulated CTL responses and therapeutic immunity against B16 melanoma by counteracting CD4 + 25 + regulatory T (Tr) cell‐mediated immunosuppression via IL‐6‐induced Foxp3 down‐regulation . This prompted us to assess the potential immunotherapeutic effect of adoptively transferred transgene IL‐6 ‐engineered DC‐stimulated CTLs with respect to the eradication of established tumors.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Therefore, these 2 cytokines when produced by baculovirus-stimulated DCs may contribute to the activation of CD4 C helper T cells and downregulation of T reg -cell function, thereby stimulating Th1-type immunity and subsequent effective induction of memory and/or effector CD8 C T cells against the tumor cells. Further research will be needed to understand the relationship between the migration of T reg cells into the tumor and the immunological activity of baculovirus.…”
Section: Discussionmentioning
confidence: 99%